Development of Nearpod-Based Interactive Media on Science Learning Style Material Theme 7 Subtheme 1 Class IV SDN 008 Sungai Kunjang - Hasniar Hasniar; La Djangka La Djangka; Rosita Putri Rahmi Haerani; Muh Ramli Buhari (Global READ Center, 2025)
Interactive media is needed in the era of revolution 4.0, because it makes easy way for teachers to educate students. Interactive media makes the learning process interesting by combining visual and audio. This study aims to determine the feasibility and response of students regarding Nearpod-Based Interactive Media in Science Learning Style Material Theme 7 Subtheme 1 Class IV SDN 008 Sungai Kunjang. The research method used is R&D (Research and Development) with the ADDIE development model. Data collection techniques with observation, interview, and questionnaire methods. The results of this study are in the form of interactive learning media that can be accessed by students in the Nearpod application that can be used anywhere and anytime. The feasibility assessment from media experts obtained a score of 86% in the very valid category, then the feasibility assessment from material experts obtained a value of 98.4% in the very valid category, and student responses obtained a value of 92.5% in the very good category. Based on the results of the feasibility test, it can be concluded that the Development of Nearpod-Based Interactive Media in Science Learning Style Material Theme 7 Subtheme 1 Class IV can be used for the real teaching media.